The Relationship Between The Blood Concentration Of Isoniazid, Rifampicin, Pyrazinamide And The Treatment Outcomes Of Pulmonary Tuberculosis Patients - Mahjoub, Abdallah Abdallah (2017)
A prospective cohort study was conducted in Hospital Pulau Pinang to find out the determinants of the pharmacokinetics of isoniazid (INH), rifampicin (RIF), and pyrazinamide (PZA), and to assess the effect of these pharmacokinetic parameters on the treatment outcomes of pulmonary tuberculosis patients. Plasma concentration of INH, RIF, and PZA was measured by new HPLC methods developed and validated as part of this study. The median of maximum plasma concentration (Cmax) of INH, RIF, and PZA was 4.75, 6.85, and 42.00 mg/L respectively. The median of the area under the time -concentration curve from zero to 24 hours (AUC0-24h) of INH and RIF was 20.1 and 33.2mg × h/ L respectively.